Conversational Implicature Engenderings in the Interaction between English Instructors - Sabrina, Arini; Sofwan, Ahmad (Universitas Negeri Semarang, 2016)
In decoding implicatures, especially conversational implicatures, interlocutors should carefully pay attention both on the literal and pragmatic meanings. This importance simultaneously affects educators to be adept at implicating a message conversationally, also at transferring it to their students. The duty gets more challenging for the ones teaching a foregin language. This study then is conducted to investigate the conversational implicatures among English instructors from Indonesia who interact using English as their foreign language. Besides, this study also endeavours to trace what maxims are flouted, and to describe the gender-based difference of implicating a message conversationally. Twelve male and twelve female English instructors were invited to voluntarily participate in informal interactions approximately for fifteen minutes without their notice on the focus of this study, revealing 140 implicatures. These are wide-ranging in terms of contents based on the topics they choose, and are similar in terms of the intended messages which are not the same as the ones have said. Moreover, the exploitations also occurr on all four maxims variously: quality, quantity, manner, and relevance. The last, female instructors are observed to implicate more frequently than male ones with the comparison between 88 and 52.